A report of dieback and mortality of elm trees suspected of Dutch elm disease in Hokkaido, Japan. Issue 6 (2nd November 2019) - Miyamoto, Toshizumi; Masuya, Hayato; Koizumi, Akio; Yamaguchi, Takehiro; Ishihara, Makoto; Yamaoka, Yuichi; Okane, Izumi; Shizuki, Mariko; Ohara, Masahiro
ABSTRACT: A sudden, increased mortality of Ulmus davidiana var. japonica (Japanese elm) trees occurred during 2014–2016 in Sapporo City, Hokkaido, Japan. The dead and dying trees were concentrated within a narrow area (maximum distance of approximately 300 m). The estimated affected tree age was 36–186 years. A previous large-scale outbreak of elm dieback in Hokkaido had been reported in the 1950s. At that time, Scolytus esuriens (elm bark beetle) was reported to be responsible for the spread of the disease; however, the actual fungal cause of the disease remained unclear. Since then, an outbreak of Japanese elm dieback of that scale has not been reported in Japan. In our study, S. esuriens adults and larvae were found in the gallery or bark of dead or dying Japanese elms. Fungal isolates obtained from S. esuriens and from the wood of the galleries were identified as Ophiostoma ulmi and O. novo-ulmi . Many weakened trees with wilting branches were present around these beetle-attacked trees. Therefore, it is suspected that Dutch elm disease caused this occurrence of Japanese elm dieback.